2020
DOI: 10.1101/2020.11.17.387340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reproductive compensation and selection among viable embryos drive the evolution of polyembryony

Abstract: Simple polyembryony – where a single gametophyte produces multiple embryos with different sires but the same maternal haplotype – is common in conifers, ferns, horsetails and other vascular plants. Polyembryony could be favored as a mechanism of reproductive compensation, providing a backup for inviable embryos, or as a mechanism of embryo competition and eliminating plants with low fitness, perhaps acting as a mechanism of Self-Incompatibility (SI). However as the evolution of polyembryony from monoembryony h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
(127 reference statements)
1
4
0
Order By: Relevance
“…For simplicity, we model reproductive compensation by providing each seed with a single backup - such that if the first ‘primary’ seed is inviable, it can be replaced by another, which may or may not be viable. This roughly follows the case of polyembryony in pines which we modeled previously (25), with the distinction that in this model maternal half-sibs do not necessarily inherit the same maternal allele. For tractability, we further assume that inbreeding depression is expressed after seed development (such that initially all embryos live to become full seeds), and that this inbreeding depression is both unpurgeable (i.e.…”
Section: Methods and Modelssupporting
confidence: 70%
See 3 more Smart Citations
“…For simplicity, we model reproductive compensation by providing each seed with a single backup - such that if the first ‘primary’ seed is inviable, it can be replaced by another, which may or may not be viable. This roughly follows the case of polyembryony in pines which we modeled previously (25), with the distinction that in this model maternal half-sibs do not necessarily inherit the same maternal allele. For tractability, we further assume that inbreeding depression is expressed after seed development (such that initially all embryos live to become full seeds), and that this inbreeding depression is both unpurgeable (i.e.…”
Section: Methods and Modelssupporting
confidence: 70%
“…Such a scenario is likely found in polyembryonic gymnosperms which lack a self-incompatibility mechanism, cannot avoid geitonogamous selfing, and display high inbreeding depression (30). In fact, a recent study of the evolution of polyembryony (25) found a subtle shift towards an excess of common alleles that decrease embryonic fitness when there is reproductive compensation and embryos do not compete. Taken together, these two studies suggest that (i) reproductive compensation is initially favored as a mechanism to make up for inviable embryos (25), and (ii) the opportunity for reproductive compensation can further favor early inviability of inbred embryos.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Where female gametophytes with many archegonia have access to sperm from multiple individuals, as in ferns receiving sperm from numerous neighbours or in gymnosperms receiving numerous pollen grains, multiple embryos may form with identical maternal haploid genotypes, but different sires. As only one sporophyte usually survives, the sperm genotypes compete (as diploids) in an identical maternal background [22]. In bryophytes, the possibility of female choice has recently been raised and that the male genotype may influence the amount of nutrients a female allocates to a particular sporophyte [6].…”
Section: Some Features Of Plants and Their Consequencesmentioning
confidence: 99%